2017
DOI: 10.1021/acs.oprd.7b00171
|View full text |Cite
|
Sign up to set email alerts
|

(Chloromethyl)dimethylchlorosilane–KF: A Two-Step Solution to the Selectivity Problem in the Methylation of a Pyrimidone Intermediate en Route to Raltegravir

Abstract: The present work describes a two-step process, namely, silylation with (chloro­methyl)­dimethyl­chloro­silane and desilylation, to address the selectivity problem in the N-methylation of a pyrimidone intermediate toward the synthesis of the raltegravir active pharmaceutical ingredient. The said methodology delivers the desired drug substance in which the O-methylated impurity content is below the detection limit by high-performance liquid chromatography analysis. Moreover, this two-step, one-pot procedure prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Wang et al, [53] reported synthesis of intermediate 10 using commercially available starting material 2-aminoisobutyric acid. Loannis et al, [54] reported N-methylation of hexadimethylsilazide to obtain intermediate 28 (Scheme 6) which on deprotection of amine afforded 29 and reaction with oxidazole carboxylic acid (30) gave Raltegravir (2).…”
Section: Synthetic Routes Of Raltegravir (2)mentioning
confidence: 99%
“…Wang et al, [53] reported synthesis of intermediate 10 using commercially available starting material 2-aminoisobutyric acid. Loannis et al, [54] reported N-methylation of hexadimethylsilazide to obtain intermediate 28 (Scheme 6) which on deprotection of amine afforded 29 and reaction with oxidazole carboxylic acid (30) gave Raltegravir (2).…”
Section: Synthetic Routes Of Raltegravir (2)mentioning
confidence: 99%
“…The strategy was applied by Koftis and co‐workers at Pharmathen to synthesize raltegravir potassium salt (Isentress®) (Scheme ), an HIV integrase inhibitor that is manufactured by Merck & Co . A major challenge in the synthesis of raltegravir is the selective N‐methylation of the pyrimidone intermediate 228 .…”
Section: N‐methylationmentioning
confidence: 99%
“…25 Recently, we reported a mild, green and chemoselective direct photochemical aerobic oxidation of sulfides to the corresponding sulfoxides. 26 Our experience in developing operationally simple and safe protocols easily applied in industrial scale productions 27 led us to upgrade our methodology to a sustainable and industry-friendly protocol. Herein, we report environmental, novel, green and sustainable protocols for the oxidation of sulfides using a mild oxidant, such as molecular oxygen, in the presence of a low-cost commercially available photocatalyst.…”
Section: Introductionmentioning
confidence: 99%